Analisis Jaringan LAN Menggunakan Teknologi EtherChannel untuk Meningkatkan Performa Jaringan pada SMK Kartika XX-I Makassar - Fadhlirrahman Baso; Nurul Hanifa A; Andi Shelma Putri Azzahra; Nur Aisyah Mukhtar (Progressive Information, Security, Computer, and Embedded System, 2023)
We often encounter network quality decreasing over time due to the increasing number of users using the same amount of bandwidth. The decrease in network quality is due to the increase in the number of network users, with this happening a solution is also provided using the concept of utilizing the technology found in EtherChannel. There are also two options for using this technology, namely the PagP (Port Aggregation Protocol) and LACP (Line Aggregation Control Protocol) protocols. By raising this problem, it aims to test the level of network quality using the PagP and LACP protocols. This test was carried out using the client-server concept, which uses an FTP server application as a container for data transfer or data exchange, while the VLC software application is used as a streaming service. The value generated by the PagP protocol is much better than LACP when compared to using FTP services.